2010
DOI: 10.1115/1.3204586
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Heat Transfer in Automotive Turbochargers

Abstract: Heat transfers in an automotive turbocharger comprise significant energy flows, but are rarely measured or accounted for in any turbocharger performance assessment. Existing measurements suggest that the difference in turbine efficiency calculated in the conventional way, by means of the fluid temperature change, under adiabatic conditions differs considerably from the usual diabatic test conditions, particularly at low turbine pressure ratio. In the work described in this paper, three commercial turbochargers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 4 publications
0
51
0
1
Order By: Relevance
“…Cormerais et al (2006) presented the most extreme changes in operating conditions, varying turbine inlet temperature from 50°C to 500°C with a thermally insulated turbocharger and observed up to 15% points change in apparent compressor efficiency. Baines et al (2010) measured losses of 700 W at 250°C turbine inlet gas temperature (TIT) which is considerably lower than the 2.7 kW measured for a similar turbocharger by Aghaali and Angstrom with turbine inlet temperatures ranging 620-850°C (Aghaali and Angstrom, 2013). Baines et al (2010) also estimated heat transfer to ambient as 25% of total turbine heat transfer, however at 700°C TIT, where temperature gradients to ambient were much higher, Shaaban (2004) estimated this at 70%.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…Cormerais et al (2006) presented the most extreme changes in operating conditions, varying turbine inlet temperature from 50°C to 500°C with a thermally insulated turbocharger and observed up to 15% points change in apparent compressor efficiency. Baines et al (2010) measured losses of 700 W at 250°C turbine inlet gas temperature (TIT) which is considerably lower than the 2.7 kW measured for a similar turbocharger by Aghaali and Angstrom with turbine inlet temperatures ranging 620-850°C (Aghaali and Angstrom, 2013). Baines et al (2010) also estimated heat transfer to ambient as 25% of total turbine heat transfer, however at 700°C TIT, where temperature gradients to ambient were much higher, Shaaban (2004) estimated this at 70%.…”
Section: Introductionmentioning
confidence: 92%
“…Baines et al (2010) measured losses of 700 W at 250°C turbine inlet gas temperature (TIT) which is considerably lower than the 2.7 kW measured for a similar turbocharger by Aghaali and Angstrom with turbine inlet temperatures ranging 620-850°C (Aghaali and Angstrom, 2013). Baines et al (2010) also estimated heat transfer to ambient as 25% of total turbine heat transfer, however at 700°C TIT, where temperature gradients to ambient were much higher, Shaaban (2004) estimated this at 70%.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…However, studies have shown that thermal energy transfer from the turbocharger turbine seriously affects the turbine power and in turn affects the overall turbocharger performance [4][5][6]. On the other hand, experimental data from several studies have shown that insulating the turbocharger turbine can significantly improve the non-adiabatic performance of the turbocharger and hence the overall engine efficiency [4,7,8].…”
Section: Introductionmentioning
confidence: 99%